Conventional 4-field box radiotherapy technique for cancer cervix: potential for geographic miss without CECT scan-based planning. Issue 5 (1st August 2004) - Nagar, Y. S.; Singh, S.; Kumar, S.; Lal, P.
Abstract : Background: The advantage of 4-field radiation to the pelvis is that the use of lateral portals spares a portion of the small bowel anteriorly and rectum posteriorly. The standard lateral portals defined in textbooks are not always adequate especially in advanced cancer cervix. Methods: An analysis was done to determine adequacy of margins of standard lateral pelvic portals with CECT defined tumor volumes. The study included 40 patients of FIGO stage IIB and IIIB treated definitively for cancer cervix between 1998 and 2000. An inadequate margin was defined if the cervical growth and uterus were not encompassed by the 95% isodose. Results: An inadequate posterior margin was common with bulky disease ( P = 0.06) and with retroverted uterus ( P = 0.08). Menopausal status, FIGO stage, associated myoma, and age were of no apparent prognostic significance. Bulk retained significant on multivariate analysis. An inadequate anterior margin was common in premenopausal ( P = 0.01); anteverted uterus ( P = 0.02); associated myoma ( P = 0.01); and younger patients ( P = 0.03). It was not influenced by bulk or stage. Menopausal status and associated myoma retained significant on multivariate analysis. Conclusion: Without the knowledge of precise tumor volume, the 4-field technique with standard portals is potentially risky as it may under dose the tumor through lateral portals and the standard AP/ PA portals are a safer option.